An Update on Candida tropicalis Based on Basic and Clinical Approaches - Zuza-Alves, Diana L.; Silva-Rocha, Walicyranison P.; Chaves, Guilherme M. (Frontiers in Microbiology, 2017)
Candida tropicalis has emerged as one of the most important Candida spp. It has been widely considered the second most virulent Candida species, only preceded by C. albicans. Besides, this species has been recognized as a very strong biofilm producer, surpassing C. albicans in most of the studies. In addition, it produces a wide range of other virulence factors, including: adhesion to buccal epithelial and endothelial cells; the secretion of lytic enzymes, such as proteinases, phospholipases and hemolysins, bud-to-hyphae transition (also called morphogenesis) and the phenomenon called phenotypic switching. This is a species very closely related to C. albicans and has been easily identified with both phenotypic and molecular methods. In addition, no cryptic sibling species were yet described in the literature, what is contradictory to some other medically important Candida species. C. tropicalis a high clinical importance and may be the second or third etiological agent of candidemia, specifically in Latin American Countries and Asia. Resistance to the azoles, polyenes and echinocandins has already been described. Apart from all these characteristics, C. tropicalis has been considered an osmotolerant microorganism and this ability to survive to high cells concentration may be important for fungal persistence in saline environments. This physiological characteristic makes this species suitable for use in biotechnology processes. Here we describe an update of C. tropicalis, focusing on all these previously mentioned subjects.